Long-term outcome after adding an ICD to CRT in non-ischemic patients. (14th October 2021) - Veres, B; Schwertner, W; Tokodi, M; Kuthi, L; Merkel, E.D; Behon, A; Zima, E; Osztheimer, I; Geller, L; Kovacs, A; Kosztin, A; Merkely, B
Abstract: Background: There are limited and contradictory data on the long-term mortality benefit of cardiac resyncronization therapy with implantable cardioverter defibrillator (CRT-D)as compared to Cardiac resynchonization therapy with pacemaker. Purpose: Our aim was to evaluate the long-term all-cause mortality benefit of CRT-D compared to CRT-P by ischemic aetiology. Methods: Between 2000 and 2018, patients, who underwent successful CRT implantation were registered. From 2524 patients, 1366 (54%) had a CRT-D implantation and 1099 (44%) had CRT-P implantation. 59 (2%) patients were excluded from the current analysis, who had an ICD upgrade with a CRT-P device during the follow-up. The primary composite endpoint was all-cause mortality, LVAD implantation or heart transplantation. Kaplan-Meier and multivariate Cox regression analyses were used to assess all-cause mortality in the total cohort and by ischemic aetiology. Results: The median follow-up time was 3.6 years. During this time 1389 patients died from any cause, 692 patients (50%) with a CRT-D device, and 697 patients (50%) with a CRT-P. Patients in the CRT-D group were younger (67 years vs. 70 years; p<0.001), had a less advanced functional class (NYHA III/IV., 52.2% vs. 61.4%; p<0.001), wider QRS [160ms (140/180) vs. 160ms (140/170); p=0.03] and less females (18.9% vs. 33.3%; p<0.001) with an ischemic aetiology (57.7% vs. 40.2%; p<0.0001). CRT-D patients had a better renal function [eGFR, 60.5 (ml/min/1.73m 2 ) vs. 57 (ml/min/1.73m 2 ); p=0.02], decreased ejection fraction (28% vs. 30%; p=0.002), had more frequently ventricular arrhythmia (36% vs. 9.8%; p<0.001). CRT-D patients took more amount of beta-blockers (90.2% vs. 87.3%; p=0.03), MRA (72.2% vs. 61.6%; p<0.001) and amiodaron (32.2% vs. 20%; p<0.001). By multivariate analysis in the total cohort gender, renal function, functional class, aetiology, and the presence of ICD were independent predictors of all-cause mortality. By multivariate analysis, patients with a CRT-D device showed a 25% decreased risk of long-term mortality compared to CRT-P alone in the total cohort. (aHR 0.75; 95% CI 0.58–0.97; p=0.03). When patients were analysed by their etiology, those with non-ischemic cardiomyopathy showed a significant mortality benefit from ICD even after adjusting for relevant clinical variables (aHR 0.45; 95% CI 0.28–0.72; p<0.01). In ischemic patients despite of having a clear mid-term mortality benefit of ICD, it is decreasing after 5 years and less considerable after adjusting for clinical variables (aHR 0.92; 95% CI 0.67–1.27; p=0.60). Conclusions: Although, CRT-D had a notable mid-term mortality benefit in ischemic patients compared to CRT-P alone, after 5 years it became less pronounced. While in non-ischemic patients, the benefit of adding an ICD to CRT lasts over 10 years. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Project no. NVKP_16-1–2016-0017 ("National Heart Program") has been implemented with the support provided by the National Research, Development and Innovation Fund of Hungary, financed under the NVKP_16 funding scheme. The research was financed by the Thematic Excellence Programme (2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging thematic programmes of the Semmelweis University.